A method for yield and cycle time improvements in Al alloy casting with enhanced conductivity steel for die construction - Vergnano Alberto; Salvati Emanuele; Magistrelli Andrea; Brambilla Edoardo; Veronesi Paolo; Leali Francesco (Manufacturing Review, 2022)
A die for Al alloy casting must be designed to achieve the expected quality levels. Moreover, the casting unit cost must be regarded as the objective function to be minimised. It can be expressed as a function of the quantity of materials and energy to be used, cycle time and equipment investment. This work compares the performance of the die with inserts manufactured using the usual 1.2343 steel with that of the innovative 1.2383. The latter is considered due to its enhanced thermal conductivity, despite being more expensive. Simulation experiments are designed to evaluate different die layouts. The quality design solutions are evaluated against the cost objective function in order to identify the optimal die choice. A case study on gravity die casting (GDC) of an AlSi7Mg0.3 engine head shows faster solidification dynamics when using 1.2383 instead of 1.2343 steel. This reduces the feeder volume, thus increasing the production yield and speeding up the cycle time with a leverage effect. The higher investment cost for the inserts is rapidly returned thanks to the reduction in variable costs. The Return On Investment (ROI) with the improved die in the new solution is short compared with the life of the die.